Developing and Piloting a Tool to Identify Food Insecurity in Older Adults. Issue 8 (August 2019) - King, Alexandra; Roofeh, Regina; Nouryan, Christian; Zhang, Meng; Carney, Maria Torroella
Abstract : Objective: The literature shows that food insecurity (FI) can negatively affect the trajectory of many chronic illnesses. FI can be acutely severe for older adults, but screening for FI is not regularly performed in the hospital setting. Our goal was to develop a tool to screen for FI upon hospital discharge to identify patients who may require community food resources. This is the first attempt to build such a tool for implementation in our health system. Methods: In two university hospitals and one community hospital, patients 65 years old and older were admitted to the Internal Medicine service who would approach discharge within 2 days. We screened patients meeting our criteria using an FI tool (FIT), which addressed patterns associated with FI. All of the patients screened were offered a list of community resources. Results: Of the patients recruited, 69 met the study criteria. The majority of patients screened displayed some FI, with 56% having ≥3 food insecurities. Statistically significant relationships were established for individual FIT questions with age, admission albumin level, body mass index, length of stay, and median household income based on ZIP code. Conclusions: Use of the FIT can help identify vulnerable patients and connect them to food resources. The FIT was easy to use, well tolerated, and time-efficient, leaving it poised for use in the busy environment of inpatient services. Abstract : Food insecurity can be a severe problem for older adults, which can be exacerbated after an inpatient admission and can be a risk factor for noncompliance after hospital discharge. The authors developed and piloted a screening tool to identify older adults who may experience food insecurity to address this issue during an inpatient admission and connect them to community resources after discharge. The study found that the screening tool was effective in identifying older adults who may face food insecurity upon discharge and led to appropriate referrals to additional community resources.